An innovative approach of priming lignocellulosics with lytic polysaccharide mono-oxygenases prior to saccharification with glycosyl hydrolases can economize second generation ethanol process. (July 2020) - Agrawal, Dhruv; Kaur, Baljit; Kaur Brar, Kamalpreet; Chadha, Bhupinder Singh
Highlights: Heterologous expression of modular and non-modular LPMOs from A. terreus. Modular LPMO from A. terreus catalytically versatile and thermostable. Fluorescent dye tagged modular LPMO shows docking and opening of cellulose fibrils. Priming of biomass with LPMOs prior to addition of GHs enhances biomass hydrolysis. Abstract: Two Lytic polysaccharide Mono-Oxygenases (LPMOs), non-modular (PMO_08942) and modular (PMO_07920), from thermotolerant fungus Aspergillus terreus 9DR cloned and expressed in Pichia pastoris X33 and purified to homogeneity using ion-exchange chromatography were found to be of ~29 and ~40 kDa, respectively. Both LPMOs were optimally active at 50 °C; PMO_08942 was active under acidic condition (pH 5.0) and PMO_07920 at pH 7.0. Modular LPMO (PMO_07920) tethered to CBM-1 was found to be versatile as it showed appreciable activity on complex polysaccharide (both cellulose and xylans) as compared to non-modular (PMO_08942). The t1/2 of PMO_08942 (~192 h, pH 5.0) and PMO_0792 (~192 h, pH 7.0) at 50 °C, suggests highly stable nature of these LPMOs. Fluorescently tagged modular AA9 was studied microscopically to understand interaction with pretreated biomass. Priming of biomass for up to 6 h with LPMOs prior to initiating hydrolysis with core cellulase enzyme resulted in significantly higher saccharification.